Lipid Lowering Activity of Anthocephalus indicus Root in Hyperlipidemic Rats. Issue 3 (2010) - Kumar, Vishnu; Khan, Mohammad Mubin; Khanna, Ashok Kumar; Singh, Ranjana; Singh, Sushma; Chander, Ramesh; Mahdi, Farzana; Mahdi, Abbas Ali; Saxena, Jitendra Kumar; Singh, Raj Kumar
Abstract : The lipid lowering activity of Anthocephalus indicus (family Rubiaceae; Hindi name Kadamba) root extract has been studied in triton WR-1339 induced hyperlipidemia in rats. In this model, feeding with root extract (500 mg kg −1 b.w.) lowered plasma lipids and reactivated post-heparin lipolytic activity in hyperlipidemic rats. Furthermore, the root extract (50–500 μM) inhibited the generation of superoxide anions and hydroxyl radicals, in both enzymic and non-enzymic systems, in vitro . The results of the present study demonstrated both lipid lowering and antioxidant activities in root extract of A. indicus, which could help prevention of hyperlipidemia and related diseases.